TRANSPORTATION SYSTEM IN JAPAN: A LITERATURE STUDY - Geradi Yudhistira; Muhammad Iqbal Firdaus; Lira Agushinta (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2015)
In Japan, the transportation system is the lifeblood of the country in order to ease the flow of people, goods, and information, supporting the achievement of optimum economic resources allocation.  To  that  end,  the  transportation  service  should  be  fairly  evenly  available  and affordable purchasing power. This is a literature study, whose main data sources are books, literature, records, and reports that have to do with the subject matter being solved. The results show that Japanese transportation system is very modern, comfortable, secure, punctual, and well-organized, as well as outstanding in service and responsible, so that people use public transport rather than private cars. Transportation in Japan as in other countries includes land, sea, and air transports. On land, there is a transport in the form of excellent trains and become a major transportation in Japan. In addition, there are also subway trains. To connect between islands, especially the four largest islands (Hokkaido, Honshu, Shikoku, and Kyushu) there are ferries as a means of crossing. Also available is a comprehensive international air service through two major airlines, Japan Airlines and All Nippon Airways, as well as foreign airlines based  on  the  operators  who  fly  all  over  the  world.  Transportation  in  Japan  is  generally accommodated by Japan Railway (JR), the state-owned company JR Bus, JR Train, and others.